Upaya Pemberdayaan Masyarakat melalui Pelatihan Pengolahan Ikan Patin sebagai Produk Unggulan di Desa Basarang, Kecamatan Basarang, Kabupaten Kapuas - Fenroy Yedithia; Gandi Gandi; Elmalia Putri Ramadhani; Helmi Helmi; Enggi Dwi Riski; Mamik Kiki Nindasari; Tanti Siburian; Dommarya BR Padang; Septian Dwi Putra; Hizkya Alfredo Malau; Mutia Eka Angraeni; Chaterina Via Vergidiastry; Terevina Lorensia; Benediktus Iga Wihantara; Dede Pranata (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Basarang Village, located in Basarang Sub-district, Kapuas Regency, Central Kalimantan, has great potential in fisheries, particularly catfish farming. Despite the abundant production of catfish, its utilization is still limited to the sale of fresh fish without further processing. This condition encouraged KKN students from Palangka Raya University to conduct community service activities in the form of training on processing catfish into fish crackers, with the aim of increasing the added value of products and community income. The training was attended by PKK women and members of the Basarang Village Youth Organization on August 8-9, 2024. The methods used included observation, training, and coaching. The results showed high enthusiasm from the participants, as well as improved skills in catfish processing. The resulting patin fish crackers are expected to become a promising new business opportunity, strengthen the local economy, and support sustainable economic development in the village. Further implementation and policy support are needed to maximize the positive impact of this activity.